2021
DOI: 10.3390/jcm10225441
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes following Large Vessel Coronary Artery Perforation Treated with Covered Stent Implantation: Comparison between Polytetrafluoroethylene- and Polyurethane-Covered Stents (CRACK-II Registry)

Abstract: Data on the clinical outcomes comparing synthetic fluorocarbon polymer polytetrafluoroethylene- (PTFE, GraftMaster) and polyurethane- (Papyrus) covered stents (CSs) to seal coronary artery perforations (CAPs) are limited. We aimed to evaluate 30-day and 1-year clinical outcomes after PCI complicated by CAP and treated with CS. We assessed 106 consecutive patients with successful CAP sealing (122 CSs): GraftMaster (51 patients, 57 CSs) or Papyrus CS (55 patients, 65 CSs). The primary endpoint was the occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The new generation single layer PTFE-coated covered stent had also been reported 18% long-term incidence of target lesion revascularization (TLR) and without any cases of stent thrombosis in only 42.6% (n = 61) available angiographic follow-up [ 18 ]. As for PK Papyrus covered stent, the late-term outcomes seemed to be inconsistent when compared to PTFE-coated covered stent [ 23 , 27 ]. TLR in long-term follow-up were reported in prior studies, with a 16% TLR and 8% definite stent thrombosis in the SOS PK Papyrus Registry (n = 127), a 3.8% TLR with no stent thrombosis in the Spain Papyrus Registry (n = 52) and a 9.3% TLR and 4.4% stent thrombosis in the Swedish SCAAR Registry (n = 265) [ 13 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The new generation single layer PTFE-coated covered stent had also been reported 18% long-term incidence of target lesion revascularization (TLR) and without any cases of stent thrombosis in only 42.6% (n = 61) available angiographic follow-up [ 18 ]. As for PK Papyrus covered stent, the late-term outcomes seemed to be inconsistent when compared to PTFE-coated covered stent [ 23 , 27 ]. TLR in long-term follow-up were reported in prior studies, with a 16% TLR and 8% definite stent thrombosis in the SOS PK Papyrus Registry (n = 127), a 3.8% TLR with no stent thrombosis in the Spain Papyrus Registry (n = 52) and a 9.3% TLR and 4.4% stent thrombosis in the Swedish SCAAR Registry (n = 265) [ 13 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying pathogenesis of ISR in our new covered stent was inconsistent with other commercial covered stent. The construction of commercial covered stents with nondegradable membrane predisposed to increase inhomogeneous neointimal hyperplasia in the edge location and time course [ 23 , 27 ]. In the case reported by Araki et al .…”
Section: Discussionmentioning
confidence: 99%
“…The rate of major adverse events decreased with the latest generations of CSs, which are thinner and contain only one layer of metal (recent data show a target lesion revascularization rate of 5–18%, all cause death 8–20% at 1 year). 1–3 It is plausible that the larger final lumen in our LM case restored laminar flow and limited the risk of neoproliferation. Short CSs are important in bifurcations, especially in LM perforations.…”
mentioning
confidence: 80%
“…Covered stent registries and retrospective studies reported high thrombosis rates in the short-and long-term observation, ranging from 4.4-8.9% in the 1-year period to 17.8% in the 10-year follow-up [8,11]. Some of them suggested that the risk may be higher for old polytetrafluoroethylene-covered stents than for newer polyurethane-covered prostheses (9.8% vs. 1.8%, respectively); however, these results may have also been affected by the usually prolonged dual antiplatelet therapy recommended with contemporary covered stents and more potent agents prescribed nowadays [12].…”
Section: Introductionmentioning
confidence: 99%